ANALYSIS OF THE INFLUENCE OF WORK ENVIRONMENT AND LEADERSHIP STYLE ON EMPLOYEE LOYALTY WITH JOB SATISFACTION AS INTERVENING VARIABLES AT BONE ARASOE SUGAR FACTORY - Wahyunur; Mursalim Nohong; Abdul. Razak Munir (Scientia Integritas Utama, 2023)
Study This aim For analyze influence Environment Work , and Leadership Style to loyalty employee through satisfaction Work as intervening variables at Bone Arasoe Sugar Factory . Data used in study This is the primary data obtained from questionnaire . Method taking sample use method … As for the amount sample used _ a total of 113 employees remained at the Arasoe Bone Sugar Factory . Method analysis used _ is method descriptive statistical analysis and analysis path (Path Analysis) with SPSS application Version 25 for windows. The results of research on pathways First show that Environment Work and Leadership Style influential positive and significant to satisfaction work at Bone Arasoe Sugar Factory . Whereas results research on pathways second show that Environment Work , Leadership Style , and Satisfaction Work influential positive and significant to Loyalty employees at Bone Arasoe Sugar Factory .